Syntheses, Characterization, and Antimicrobial Screening of N-(benzothiazol-2-yl)benzenesulphonamide and its Cu(I), Ni(II), Mn(II), Co(II), and Zn(II) Complexes - N. L. Obasi; Okoye C. O. Benedict; P. O. Ukoha; A. O. Anaga (E-Journal of Chemistry)
N-(benzothiazol-2-yl)benzenesulphonamide (BS2ABT) was synthesized by the condensation (by refluxing) of 2-aminobenzothiazole and benzenesulphonylchloride in acetone at 140ºC. The resulting crude precipitates were recrystallized from dimethylformamide (DMF). Five metal complexes of copper(I), nickel(II), manganese(II), cobalt(II) and zinc(II) of the ligands were synthesized. The compounds were characterized using magnetic susceptibility measurements, UV/VIS spectrophotometry, infra red, proton and 13C nmr spectroscopies. The antimicrobial tests of the ligands and its metal complexes were carried out on both multi-resistant bacterial strains isolated under clinical conditions and cultured species using agar-well diffusion method. The multi-resistant bacterial strains used were Escherichia coli, Proteus species, Pseudomonas aeroginosa and Staphylococcus aureus which were isolated from dogs. The culture species were Pseudomonas aeruginosa (ATCC 27853), Escherichia Coli (ATCC 25922) Staphylococcus aureus (ATCC 25923), and the fungi, Candida krusei (ATCC 6258) and Candida albicans (ATCC 90028). The tests were both in vitro and in vivo. Thus the Inhibition Zone Diameter (IZD), the Minimum Inhibitory Concentration (MIC), and the Lethal and Effective Concentrations (LC50 and EC50) were determined. The antimicrobial activities of the compounds were compared with those of Ciprofloxacin and trimethoprim-sulphamethoxazole as antibacterial agents and Fluconazole as an antifungal drug. All the compounds showed varying activities against the cultured typed bacteria and fungi used. However, they were less active than the standard drugs used except Fluconazole which did not show any activity against Candida krusei (ATCC 6258) but most of the compounds synthesized were very active against it. The Lethal Concentration (LC50) ranged from 26.25±4.9-1833.88±186.92 ppm. These are within the permissible concentrations.